Efficacy and Safety of Systemic Treatments Among Colorectal Cancer Patients: A Network Meta-Analysis of Randomized Controlled Trials - Hoang, Tung; Sohn, Dae Kyung; Kim, Byung Chang; Cha, Yongjun; Kim, Jeongseon (Frontiers in Oncology, 2022)
Background: Systemic treatments including either monotherapy or combination therapy, are commonly administered to patients with advanced or metastatic colorectal cancer (CRC). This study aimed to provide the complete efficacy and safety profiles and ranking of systemic therapies for the treatment of unresectable advanced or metastatic CRC. Methods: We searched PubMed, Embase, the Cochrane Library, and ClinicalTrials.gov from inception until June 30, 2021, as well as the bibliographies of relevant studies. Randomized controlled trials comparing two or more treatments including at least capecitabine, 5-fluorouracil, leucovorin, irinotecan, bevacizumab, cetuximab, oxaliplatin, or panitumumab were investigated. A network meta-analysis using the Bayesian approach was performed to compare the efficacy and safety of treatments. The surface under the cumulative ranking curve (SUCRA) was calculated for the probability of each treatment as the most effective. The overall response rate (ORR), disease control rate (DCR), overall survival (OS), progression-free survival (PFS), adverse events (AEs) grade ≥3, and serious adverse events (SAEs) were evaluated. Results: One hundred two publications with 36,147 participants were assigned to 39 different treatments. Among 11 treatments with full information on six outcomes, FOLFIRI/FOLFOX/FOLFOXIRI + bevacizumab significantly improved both the ORR and DCR, compared to FOLFIRI. Although FOLFOX and FOLFIRI/FOLFOX + cetuximab significantly prolonged both OS and PFS, treatments were comparable in terms of AEs grade ≥3 and SAEs. The top highest SUCRA values were observed in the FOLFOXI + panitumumab group for ORR (96%) and DCR (99%), FOLFIRI + bevacizumab + panitumumab group for OS (62%) and PFS (54%), and FOLFOXIRI + bevacizumab group for AEs grade ≥3 (59%) and SAEs (59%) outcomes. Conclusions: These findings suggest an available range of systemic treatment therapies with different efficacy and safety profiles patients with. Further investigations of the side effects and mutation status are required to confirm our findings. PROSPERO registration number: CRD42019127772.